Interpretation of mandibular condyle fractures using 2D- and 3D-computed tomography - Costa e Silva,Adriana Paula de Andrade da (2003)
Computed tomography (CT) has been increasingly used in the examination of patients with craniofacial trauma. This technique is useful in the examination of the temporomandibular joint and allows the diagnosis of fractures of the mandibular condyle. Aiming to verify whether the three-dimensional reconstructed images from CT (3D-CT) produce more effective visual information than the two-dimensional (2D-CT) ones, we evaluated 2D-CT and 3D-CT examinations of 18 patients with mandibular condyle fractures. We observed that 2D-CT and 3D-CT reconstructed images produced similar information for the diagnosis of fractures of the mandibular condyle, although the 3D-CT allowed a better visualization of the position and displacement of bone fragments, as well as the comminution of fractures. These results, together with the possibility of refining and manipulating perspectives in 3D images, reinforce the importance of its use in the surgical planning and evaluation of treatment. We concluded that 3D-CT presented supplementary information for a more effective diagnosis of mandibular condyle fractures.